STRATEGI PENGEMBANGAN MAKANAN TRADISIONAL BALI DI HOTEL AREA SANUR-DENPASAR - Made Hendrayana (Jurnal Ilmiah Hospitality Management, 2011)
Bali traditional food becomes a rare product of food industry in Bali, even though it was qualified from the gastronomy point of view. A research about Balinese traditional food development strategies of hotels in Sanur area was conducted in order to reveal the gap.            The research was aimed to analyze the internal and external environment, to formulate the common strategy and alternative strategy, to decide the priority strategies implemented in the development of Balinese traditional food of hotels in Sanur area.            The data were analyzed by using internal-external (IE) matrix analysis and SWOT analysis, then it was continued by QSPM (Quantitative Strategic Planning Matrix) analysis in order to determine strategic priorities.            The result of the analysis of powerful factors of internal strategy shows the total score of internal factor which was 2, 97. On the other hand the total score of the external factor was 2, 70. This was indicated that the external factor was able to take advantages of opportunities, and to avoid threats.            The strength of internal environment strategies was the unique taste and aroma, product quality of Balinese traditional food. The weaknesses of internal environment strategies were the inconsistent flavor, and the small number of menu variation of Balinese traditional food.            The strength of external environment strategies was the increase of special interest tours (culinary tour), large numbers of variations and types of Balinese traditional food. The weaknesses of external environment strategies were the threat of outside product, hygiene, and sanitation.            The alternative strategies were formulated as follow: improve Balinese traditional food, maintain and improve the quality of Balinese traditional food, develop/open the traditional food stalls in hotel, improve and maintain the good image of Balinese traditional food quality, increasing the variation of Balinese traditional food in menu, implementing the quality control of Balinese traditional food, improve and maintain the consistency of food flavor, and to increase the offers of Balinese traditional food.            Priority of strategies was formulated as follow; the strategy to increase the promotion, increasing the variation of Balinese traditional food in menu were the main options. Strategies to increase the offers of the product and develop/open the traditional food stalls in hotel were the second options. To improve and maintain the consistency of food flavor, maintain and improve the quality of Balinese traditional food were the third options. Improve and maintain the good image of Balinese traditional food, the implementation of quality control, were the last options.            Synergy among owners, managers, government, society, and other party outside the tourism was needed to raise the value of Balinese traditional food and to achieve the goal of Balinese traditional food development.